JURNALISME DAMAI DALAM MEDIA DIGITAL: KONTRIBUSINYA BAGI PENCEGAHAN DAN PENYELESAIAN KONFLIK - Arif Susanto; Martha Warta (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2023)
AbstractPeace Journalism in digital media supposed to be a part of ethical values which is play a role of groundwork for a media operated in a plural society. By a warm and unprovocative news, digital media could take a part in preventing and ceasing conflicts. Aside from evaluating contributions of peace journalism, this research would like to review connectivity between media and their readers in affirming order and peace. Scrutinizing news issued by kompas.com, medcom.id and tempo.co during Ramadan 1441H, we can see that three of them tried to integrate peace journalism value in their digital publication. However, peace journalism still confronting challenges such as hoax and click bait which could entrap digital media in fulfilling their interests by sacrificing public interest in maintaining order.Â Keywords: peace journalism, digital media, conflict prevention and resolution.